An exploratory study of knowledge, attitudes, and practices toward HPV associated anal cancer among Pakistani population - Awan, Usman Ayub; Naeem, Wajiha; Khattak, Aamer Ali; Mahmood, Tahir; Kamran, Shehrish; Khan, Suliman; Guo, Xingyi; Yongjing, Zhao; Liu, Jianbo; Nasir, Abdul (Frontiers in Oncology, 2023)
Background: Anal cancer, mainly attributed to human papillomavirus (HPV) infection, is rising in prevalence among the general population in Pakistan. This study aimed to examine the knowledge, attitudes, and practices (KAP) towards anal cancer screening and HPV of the general population in Pakistan.We surveyed anal cancer KAP using social media and snowball sampling from December 2022 to May 2023. The questionnaire had 16 knowledge, 12 attitudes, 6 practice questions, and socio-demographic variables. We applied validity criteria for inclusion and exclusion and used cutoffs ≥50% for each KAP categoriescategory. We analyzed data in R with Guttman's λ2 for reliability, did univariate and bivariate analysis, and reported frequencies, percentages, p-values, coefficients, odds ratios, and 95% confidence intervals.We surveyed 1620 people and discovered low awareness of HPV and anal cancer causes, prevention, and screening (11%-24%), high stigma and embarrassment for screening (54%-70%), strong moral beliefs (89%), condom nonuse (91%), and low engagement in health services and programs (9.1%-14%). Knowledge (75.23%, OR = 1.0984, p = 0.05) was shaped by sociodemographic factors, attitude, and practice, with higher education enhancing knowledge (OR = 1.0984, p = 0.05). Attitude (78.45%, OR = 6.6052, p < 0.001) was influenced by sociodemographic factors, practice, and knowledge as well. Younger females, single, unemployed, students, living with more family members, earning more income, and residing in Islamabad had a more positive attitude (ORs from 1.0115 to 6.6052, p < 0.05), while religion did not affect attitude (p = 0.51). Practice (9.16%, OR = 0.1820, p < 0.001) was determined by socio-demographic factors, knowledge, and attitude too. Older males, employed teachers, living with more family members, earning less income, and residing in Islamabad had better practice (ORs from 0.1323 to 3.8431, p < 0.05), but marital status and religion did not influence practice (p > 0.05).Pakistani young adults need more education, awareness, health services, and programs on HPV and anal cancer, as they have low awareness, high stigma, and socio-cultural challenges. In addition, it is recommended for more research and policy initiatives are needed to address socio-cultural factors and increase anal Pap to overcome anal cancer.